CO2-measuring dongle. (October 2022) - Boillat, Marc-Aurèle; Hauser, Peter C.
Graphical abstract: Abstract: The compact pocketable CO2 -measuring device is built on a small printed circuit board (PCB) with the dimensions of ca. 8.5 × 3 cm. It is plugged into the universal serial bus (USB) port of a personal computer (PC) which serves to provide power and for downloading the measurements. The measurements can be viewed on the computer display where they also can be plotted as a graph to recognize trends. As the level of CO2 rises indoors when people are present and the air is not exchanged adequately the device can be employed as a personal device for monitoring indoor air quality. This is of particular interest when airborne pathogens might be present such as during the COVID-19 pandemic. The device utilizes a novel compact CO2 sensor which has only become available commercially recently, and is based on the photoacoustic measuring principle. A graphical user interface on the PC programmed in Python allows easy interaction with the user. A MSP430FR2433 microcontroller on the board controls the sensor and establishes the communication to the software application on the computer. This was facilitated by the choice of Forth as the programming framework for the microcontroller.